Analisis Faktor yang Mendorong Konsumen Memilih Hotel Melalui Situs Traveloka.com - Muhammad Ashoer; Munawir Nasir Hamzah; Fahrina Mustafa (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2019)
Clutching rapid penetration, Indonesia has transformed onto the biggest digital economic market throughout the world, hence it is interesting to be studied in depth. This study aims to measure factors that are considered affecting consumer online purchasing decisions which are perceived usefulness, perceived ease of use, and perceived risk. The study was conducted upon the hotel consumers who have performed online transaction via Traveloka for at least once. The sampling method used purposive sampling technique (non-probability sampling) and the number of respondents that met the criterion was set by 106 respondents. The result shows perceived usefulness and perceived ease of use have positive and significant effect on e-commerce decision, whereas perceived risk has not significant effect. The founding implicates for the improvement of new insights and better understanding to e-commerce actors, especially Traveloka by developing effective strategies to increase profit